Risk Factors for Carbapenemase-Producing Carbapenem-Resistant Enterobacteriaceae (CP-CRE) Acquisition Among Contacts of Newly Diagnosed CP-CRE Patients. (25th July 2016) - Schwartz-Neiderman, Anat; Braun, Tali; Fallach, Noga; Schwartz, David; Carmeli, Yehuda; Schechner, Vered
Abstract : OBJECTIVE: Carbapenemase-producing carbapenem-resistant Enterobacteriaceae (CP-CRE) are extremely drug-resistant pathogens. Screening of contacts of newly identified CP-CRE patients is an important step to limit further transmission. We aimed to determine the risk factors for CP-CRE acquisition among patients exposed to a CP-CRE index patient. METHODS: A matched case-control study was performed in a tertiary care hospital in Israel. The study population was comprised of patients who underwent rectal screening for CP-CRE following close contact with a newly identified CP-CRE index patient. Cases were defined as positive tests for CP-CRE. For each case patient, 2 matched controls were randomly selected from the pool of contacts who tested negative for CP-CRE following exposure to the same index case. Bivariate and multivariate analyses were conducted using conditional logistic regression. RESULTS: In total, 53 positive contacts were identified in 40 unique investigations (896 tests performed on 735 contacts) between October 6, 2008, and June 7, 2012. bla KPC was the only carbapenemase identified. In multivariate analysis, risk factors for CP-CRE acquisition among contacts were (1) contact with an index patient for ≥3 days (odds ratio [OR], 9.8; 95% confidence interval [CI], 2.0–48.9), (2) mechanical ventilation (OR, 4.1; 95% CI, 1.4–11.9), and (3) carriage or infection with another multidrug-resistant organism (MDRO; OR, 2.6; 95% CI, 1.0–7.1). Among patients who received antibiotics, cephalosporins were associated with a lower risk of acquisition. CONCLUSIONS: Patient characteristics (ventilation and carriage of another MDRO) as well as duration of contact are risk factors for CP-CRE acquisition among contacts. The role of cephalosporins requires further study. Infect Control Hosp Epidemiol 2016;1–7